Price rigidities and the granular origins of aggregate fluctuations - Ernesto Pasten; Raphael Schoenle; Michael Weber (European Central Bank (ECB), 2017)
We study the aggregate implications of sectoral shocks in a multi-sector New Keynesian model featuring sectoral heterogeneity in price stickiness, sector size, and input-output linkages. We calibrate a 341 sector version of the model to the United States. Both theoretically and empirically, sectoral heterogeneity in price rigidity (i) generates sizable GDP volatility from sectoral shocks, (ii) amplifles both the " and the etwork" effects, (iii) alters the identity and relative contributions of the most important sectors for aggregate fluctuations, (iv) can change the sign of fluctuations, (v) invalidates the Hulten (1978) Theorem, and (vi) generates a " origin of aggregate fluctuations.
Keywords: E31; E32; O40; 330; Input-output linkages; sticky prices; idiosyncratic shocks